Green finance, new infrastructure, and carbon emission performance in Chinese cities - Li, Hao; Yang, Zihan; An, Jiahao (Frontiers in Environmental Science, 2024)
Green finance (GF), new infrastructure (NI), and low-carbon green development play important roles in promoting high-quality economic development in China. Currently, few studies have considered the relationship between GF, NI, and carbon emission performance (CEP) simultaneously. Using the panel data of 285 Chinese cities from 2011 to 2021, an improved vertical and horizontal pull-out gearing method was used to measure the GF and NI composite indices, and CEP was measured using the SBM non-expected output model. Through the panel data fixed effect model and interactive effect model, it was found that both GF and NI can effectively enhance urban CEP and produce a superposition effect, promoting each other to deepen their ability to enhance CEP. Heterogeneity analysis shows that the effects of GF and NI are more obvious in eastern China, with a higher degree of marketisation, policy support for the development of the digital economy, and resource-based cities. Green technological innovation, industrial structure upgrading, and resource allocation optimisation are pathways for GF and NI to jointly enhance CEP. Further analysis of the spatial system of the equations model using GS3SLS methodology found that there were spatial interaction spillover effects between the three, and that these effects were better for a local area than for the surrounding neighbouring cities.